Identification of Musical Talent in Schoolchildren of the Autonomous Community of the Region of Murcia, Spain - Lázaro-Tortosa, Francisco Rafael (2021)
This work arises from the belief in the need to identify the musical talents of schoolchildren; the work follows the axiom of the theory of multiple intelligences that true integral development is achieved attending all the intelligences. The identification was carried out in primary schools of the Autonomous Community of the Region of Murcia (Spain); the schools were selected according to a stratified and multi-stage process. The participants were 932 students between the ages of ten and twelve from different public and private-subsidized educational centers. The instrument used was the Musical Aptitude Test (Seashore et al., 2008), whose scores obtained were analyzed with the Castelló and Batlle’s High Cognitive Capability Identification Model. In this autonomous community, the results indicate that there are students with musical intellectual resources of high ability and that the highest-rated qualities are tone, rhythm, and time in simple talent and rhythm and time in complex talent.